Impact of Socioeconomic Factors on Prognosis and Clinical Management in Patients with Hepatocellular Carcinoma - Su, Bing-Bing; Zhou, Bao-Huan; Bai, Dou-Sheng; Qian, Jian-Jun; Zhang, Chi; Jin, Sheng-Jie; Jiang, Guo-Qing (Turkish Journal of Gastroenterology, 2021)
Background: The prognosis for patient survival using the tumor–node–metastasis (TNM) staging system may be imperfect, as it basedonly on biological factors and does not include the socioeconomic factors (SEFs). We integrated the SEFs into the TNM system (TNMSEF),and evaluated whether the novel TNM-SEF staging system showed better prediction capacity and improved clinical guidance inhepatocellular carcinoma (HCC).Methods: We selected data of 12 514 cases with HCC between 2010 and 2015 from the SEER database. The Kaplan–Meier survivalcurves and Cox proportional hazards regression were used to analyze cancer-specific survival (CSS) among the TNM-SEF stages.Results: Multivariate Cox analyses showed that insurance status, marital status, year of diagnosis, and income were prominent prognosticSEFs (all P < .05). When compared with the SEF0 stage, the SEF1 stage was significantly associated with a 36.1% increased riskof cancer-specific mortality in HCC overall, a 22.2% increased risk of metastatic HCC, and a 41.8% increased risk of non-metastaticHCC (all P < .001). The concordance index of the TNM-SEF stage (0.768) was better than that of the TNM stage (0.764). Furthermore,patients with SEF0 stage showed higher 5-year CSS than those with SEF1 stage (I: 48.7% vs. 28.1%; II: 41.0% vs. 25.1%; IIIA: 12.8% vs.5.0%; IIIB: 7.8% vs. 6.0%; IIIC: 6.4% vs. 6.7%; IVA: 8.4% vs. 2.5%; IVB: 2.1% vs. 0.8%; all P < .05).Conclusion: We have proved that the SEF stage is an independent predictor for HCC. The combined SEF stage with TNM staging warrantsmore clinical attention, for improved prognostic prediction and clinical guidance.